2013
DOI: 10.1039/c3ra21904f
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis and screening of novel 1,3,4-oxadiazoles as potent and selective antifungal agents

Abstract: The electrochemical oxidation of aldehyde-N-aroylhydrazone has been studied in the presence of NaClO 4 as supporting electrolyte in MeOH solution using cyclic voltammetry and controlled potential electrolysis.The results indicate that intramolecular cyclization of aldehyde-N-aroylhydrazone has been successfully performed at a platinum electrode in an undivided cell with good yields of the corresponding 1,3,4oxadiazoles at ambient conditions. The reaction products were characterized by spectroscopic methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…After optimization, it was revealed that carrying out the reaction in methanol using NaClO4 as supporting electrolyte gave the highest yields. Good to excellent yields ranging from 57% to 94% were obtained 65 . 34 .…”
Section: Electrosynthesis Of Hydrazonesmentioning
confidence: 96%
“…After optimization, it was revealed that carrying out the reaction in methanol using NaClO4 as supporting electrolyte gave the highest yields. Good to excellent yields ranging from 57% to 94% were obtained 65 . 34 .…”
Section: Electrosynthesis Of Hydrazonesmentioning
confidence: 96%
“…A 50‐mL beaker‐type cell consists of a mixture of aromatic aldehyde (2 mmol), barbituric acid (2 mmol), and 1,3 dicarbonyl compounds (2 mmol) (Scheme ) stirred in water media with tetrabutylammonium iodide (1 mmol) as an electrolyte under constant potential electrolysis at room temperature for 1‐ to 2‐hour assembly with platinum plates (1 cm 2 ) as working as well as counter electrodes and an SCE as reference electrode. The completion of the reaction was confirmed by thin‐layer chromatography (TLC) plate at regular breaks of time.…”
Section: Constant Potential Electrolysismentioning
confidence: 99%
“…Literature is flooded with the construction of this scaffold and nearly 686 patents have been filed since last decade thus highlighting/capturing accelerated interest from several research groups due to the myriad applications of this system . Symmetrically and unsymmetrically 2,5‐disubstituted‐1,3,4‐oxadiazoles are encompassed with an array of broad spectrum of activities such as analgesic, antidiabetic, anticancer, antifungal, anti‐inflammatory, antitubercular, antibacterial, antiepileptic, anti‐HIV, ulcerogenic, hypoglycemic, sedative, hypnotic and insecticidal agents . Further, oxadiazoles serves as very good bioisosteres of esters, amides which makes better hydrogen bonding interactions with different receptors thereby enhancing the biological responses to a remarkable extent and resistant to enzyme‐catalyzed hydrolysis .…”
Section: Introductionmentioning
confidence: 99%